COVID-19 LOCKDOWNS AND TELEHEALTH CONSULTATION IN WEIGHT MANAGEMENT OF PATIENTS ATTENDING THE HEALTHY WEIGHT CLINIC AT MACQUARIE UNIVERSITY HOSPITAL - Woodley, Jack; Chen, Juliana; Trajkovski, Carly; Hoffman, Amy; Lord, Reginald (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Emerging literature suggests that the general Australian adult population experienced weight gain during the COVID-19 period. The primary aim of this study was to quantify changes to weight and body composition in an Australian Healthy Weight Clinic (HWC) over the COVID-19 period. Our secondary aim was to explore how lifestyle factors during periods of lockdown influenced anthropometric outcomes. METHODOLOGY The study period spanned December 2019 – December 2021. This period included two government-mandated lockdowns in March-June 2020 and June-September 2021. A retrospective chart review was conducted to extract weight and BMI outcomes from electronic patient records, while fat mass and skeletal muscle mass outcomes were extracted using SOZO bioimpedance spectroscopy. All outcomes were measured at three-month intervals. A patient survey based on current literature exploring lifestyle factors including eating and exercise, sources of stress and use of telehealth consultations was emailed to all currently enrolled clinic patients. RESULTS A total of 51 respondents were included in the quantitative arm and 229 survey responses were recorded. Weight decrease was linear and significant (p=<0.001) throughout the study period for the overall group. Average weight loss across the group was 15.7 kg (SD = 4.1 kg). No gender difference was observed. Fat mass % decrease followed a quadratic pattern (p=0.05). Among the most significant lifestyle factors were snacking, reduction in commute time and at-home childcare. Majority (65%) of participants who answered the questionnaire in full reported that telehealth consultations were useful in keeping them on track with prescribed diet and exercise regimes. CONCLUSION Despite disruptions to lifestyle and in-pehaven consultation, it appears that the implementation of telehealth appointments across our clinical services has been effective in assisting weight management at the clinical level. The efficacy of these services beyond the context of stay-at-home orders is promising and warrants further investigation.